Automatic Statistics Measurement Antenna Performance Towards Virtual Ground Station. Issue 1 (July 2020) - Hidayat, Arif; Gunawan, Hidayat; Syahputra Nasution, Ali; Andrianingsih; Wahyudi, Diki
Abstract: Ground station systems have expensive maintenance costs, the system should always be ready to receive remote sensing satellite data. The emergence of ground station discourse where earth station antennas are placed in remote areas, to obtain satellite data according to the desired strategic area. The high operational costs and reliability of the equipment, in tracking satellite and recording the remote sensing data need to monitoring and analyzing continually. System and reliability can be analyzed from the satellite data reception log. This remote-based system requires an analysis system that is able to work to automatically collect log data from several antennas and display it easily so that it can be learned without having to check each log antenna one by one. This system facilitates detection when anomaly occurs on the antenna. The statistical method is used in analyzing the antenna so that it can be known the average receive signal level parameter in the receiver, the maximum value along with azimuth and elevation. This system can see the average antenna capability and the condition of the antenna when it is not optimal. The monitoring should be automatic to locate problems in data acquisition. This system is proposed to virtual ground station.